ИСМАЙЫЛБЕК ГАСПИРАЛИНИҢ ТӘЛИМ-ТӘРБИЯЛЫҚ ОЙ-ПИКИРЛЕРИ - Сейтмуратов, Қ. (FAN va JAMIYAT, 2023)
The article deals with the origin and development, goals and objectives of the Jadid movement, the merits of the Crimean-Tatar poet and educator Ismailbek Gaspirali as a great thinker and the founder of the Jadid movement, his thoughts on the achievement of independence, his merits before the Turkic-speaking peoples.